Does the use of inhaled corticosteroids in asthma benefit lung function in the long-term? A systematic review and meta-analysis. (20th January 2021) - Tan, Daniel J.; Bui, Din S.; Dai, Xin; Lodge, Caroline J.; Lowe, Adrian J.; Thomas, Paul S.; Jarvis, Deborah; Abramson, Michael J.; Walters, E. Haydn; Perret, Jennifer L.; Dharmage, Shyamali C.
While asthma is known to be associated with an increased risk of progressive lung function impairments and fixed airflow obstruction, there is ongoing debate on whether inhaled corticosteroids (ICS) modify these long-term risks. Searches were performed of the PubMed, Embase and CENTRAL databases up to 22 July 2019 for studies with follow-up ≥1 year that investigated the effects of maintenance ICS on changes in lung function in asthma. Inclusion criteria were met by 13 randomised controlled trials (RCTs) (n=11 678) and 11 observational studies (n=3720). Median (interquartile range) follow-up was 1.0 (1–4) and 8.4 (3–28) years, respectively. In the RCTs, predominantly in individuals with mild asthma, ICS use was associated with improved pre-bronchodilator (BD) forced expiratory volume in 1 s (FEV1 ) across all age groups (2.22% predicted (95% CI 1.32–3.12), n=8332), with similar estimates of strength in association for children and adults. Improvements in post-BD FEV1 were observed in adults (1.54% (0.87–2.21), n=3970), but not in children (0.20% (−0.49–0.90), n=3924) (subgroup difference, p=0.006). Estimates were similar between smokers and nonsmokers. There were no RCT data on incidence of fixed airflow obstruction. In the observational studies, ICS use was associated with improved pre-BD FEV1 in children and adults. There were limited observational data for post-BD outcomes. In patients with mild asthma, maintenance ICS are associated with modest, age-dependent improvements in long-term lung function, representing an added benefit to the broader clinical actions of ICS in asthma. There is currently insufficient evidence to determine whether treatment reduces incidence of fixed airflow obstruction in later life. In patients with mild asthma, maintenance inhaled corticosteroids are associated with modest age-dependent improvements in long-term lung function https://bit.ly/32K2ZTF